Estresse pré-natal e exercício físico maternal : repercussões comportamentais, inflamatórias e de regulação central do eixo hipotálamo-hipófise-adrenal em camundongos - Luft, Carolina (2021)
Stressors comprise a range of adverse abilities that can be emotional or physical. The hypothalamic-pituitary-adrenal (HPA) axis is the controlling center for the production and secretion of corticosteroids during basal or stressful situations. The physiological concept of programming has been used extensively to explain the associations between prenatal stressful events, altered fetal growth, and increased vulnerability to metabolic, cognitive, and neuroendocrine disorders throughout life. In addition, studies have demonstrated that individuals physically fit and that frequently practice physical activities exhibit a lower rate of health problems, especially when faced with stressful situations. Thus, the main objective of present work was to evaluate behavioral, inflammatory, and central regulatory repercussions of the HPA axis in response to prenatal stress and to the practice of maternal physical exercise in Balb/c mice. In the first study, we have identified that the experimental model of restraint stress used was able to promote alterations in the brain glucose metabolism. These findings were observed from the decreased 18F-FDG absorption in different brain regions of males and females evaluated through microPET. In the second study, we have observed that restraint stress, when applied during pregnancy, promoted significant changes in maternal behavior and gene/protein expression of inflammatory mediators in the olfactory bulb during lactation. In the third study, we have found that the same stress model, when applied during pregnancy, altered cell mortality, autophagy, gene expression, oxidative stress, and inflammation in cortical neurons in the neonatal period. The fourth study indicated that physical exercise has a protective effect on both maternal behavior and the regulation of markers responsible for the stress response in the placenta and brain of prenatally stressed neonatal mice. The results obtained from these studies demonstrate that stress during pregnancy generated several alterations on behavior, inflammation, and in the regulation of markers involved in the modulation of the HPA axis. In addition, maternal physical exercise plays an important role in the modulation of maternal-fetal health, contributing to the prevention of neurodevelopmental changes induced by prenatal stress.